The Nature of Psychosocial Environment in Arabic Classroom among Malaysian Public Universities - Mohd Ala-Uddin, Othman; Che Mohd Zaid, .; Jumadil, Saputra (2020)
This study discusses the nature of the psychosocial environment for learning the Arabic language in the classroom among Malaysian public universities. This research is significant because mastery of the Arabic language among students is crucial, which is seldom observed in the aspects of teaching and learning only. A total of 494 students from eight Malaysian public universities participated in this study, and the research instrument adopted from Fraser. It consists of six elements, which are Students’ Cohesiveness, Lecturer’s Guidance, Involvement, Task Orientation Collaboration, and Equity. The data analyzed using descriptive statistics and Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) by assisting the Statistical Package for the Social Science (SPSS-22). The results of this study showed that the nature of the psychosocial learning environment for learning the Arabic language in the classroom interpreted to derive an analysis of perception scores. Despite positive views from the Malaysian public university students in the classroom environments for Arabic language learning, they are hopeful for an improvement in the six elements of the classroom learning environment.